The burden of pediatric emergency departments, constipation: a systematic review - Emine Özdemir Kaçer; İlker Kaçer (SpringerOpen, 2022)
Abstract Background Constipation constitutes an important part of emergency service applications in our country as well as all over the world. We aimed to illuminate the situation in our regional hospital regarding the increase in the emergency department density and the financial burden of applications due to constipation. Methods This descriptive retrospective study was conducted in a regional tertiary hospital. The medical records of all constipation-related admissions to the emergency department between 01 January 2019 and 31 December 2019 were retrospectively reviewed. The etiology of constipation, complaints, physical examination, imaging studies, treatment modalities, and health expenses costs were recorded. Results A total of 3271 patients aged 0-17 years (mean 4.24 ± 3.56 years) were included in the study. One thousand nine hundred and seventy-six (60.3%) of the patients were male, and 1295 (39.6%) of them were female. The majority of patients (n = 3107, 95%) were discharged without hospitalization. Health expenditure due to constipation was 834.626 Turkish liras. The health cost of the patients who were treated from the emergency room without hospitalization was 780.126 Turkish liras. Conclusions In order to reduce unnecessary constipation applications and costs in emergency services, more detailed information should be given to prevent constipation during outpatient services, and dietary counseling should be provided when necessary.